2010
DOI: 10.1007/s00259-010-1611-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of 18F-FDG PET/CT in the assessment of suspected recurrent gastric cancer after initial surgical resection: can the results of FDG PET/CT influence patients’ treatment decision making?

Abstract: FDG PET/CT is a superior post-therapy surveillance modality for the diagnosis of recurrent gastric cancer compared with diagnostic CT imaging after initial surgery. In addition, integrated FDG PET/CT was specifically helpful in optimizing the treatment plan and it might play an important role in treatment stratification in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…Park et al [19] reported that the sensitivity, specificity, positive predictive value, negative predictive value and accuracy of PET/CT for diagnosing true recurrence of gastric cancer were 75%, 77%, 89%, 55% and 75%, respectively. In a study of contrast-enhanced FDG PET/CT, Bilici et al [12] reported superior diagnostic performance of FDG PET/CT over CECT. Although FDG PET/CT has been used for detecting recurrent gastric cancer, several limitations have been suggested for evaluating the remnant stomach.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Park et al [19] reported that the sensitivity, specificity, positive predictive value, negative predictive value and accuracy of PET/CT for diagnosing true recurrence of gastric cancer were 75%, 77%, 89%, 55% and 75%, respectively. In a study of contrast-enhanced FDG PET/CT, Bilici et al [12] reported superior diagnostic performance of FDG PET/CT over CECT. Although FDG PET/CT has been used for detecting recurrent gastric cancer, several limitations have been suggested for evaluating the remnant stomach.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite advances in the management of recurrent gastric cancer, several studies have reported a poor prognosis for patients with recurrent gastric cancer [2,5,7,9,10]. Imaging modalities, including contrast-enhanced computed tomography (CECT) and endoscopy, have been used for the detection of gastric cancer recurrence [4,11,12]. However, a gold standard modality has not been established.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations